Continuity of Midwifery Care for Mrs. P at the Ibrahim Adjie Community Health Center, Bandung City - Nurul Chairunisa; Chris Sriyanti; Ferina Ferina; Wiwin Widayani (JURNAL IMPLEMENTA HUSADA, 2026)
Continuity of midwifery care is holistic care that builds trusting relationships, understands women's needs, and empowers them in their reproductive health care. Pregnancy, childbirth, postpartum, and breastfeeding are fundamentally physiological processes, but they can lead to discomfort. Midwives strive to help address these issues. This report aims to demonstrate continuity of midwifery care through the application of warm compresses to address discomfort occurring during pregnancy and postpartum. This report uses a case study method. Data collection was conducted from July to November 2024 at the Ibrahim Adjie Community Health Center in Bandung City. The results of continuous midwifery care for Mrs. P revealed lower abdominal pain that occurred during the third trimester of pregnancy. The delivery process was also closely related to physiological pain, which proceeded normally without complications. In the postpartum period, complaints of pain or afterpain were reported. Untreated pain can lead to anxiety and stress. Warm compresses are one method that can reduce pain simply without side effects and is in accordance with the midwife's competence. The application of warm compresses is an effective and safe non-pharmacological method for managing pain complaints during pregnancy, childbirth, and the postpartum period.